Talentos esportivos no ensino fundamental: (re)pensando as altas habilidades ou superdotação no esporte - Miranda, Guacira Quirino (2019)
Students with cues of high ability and/or gifted in sports are those who express abilities (in the body-kinesthetic / sensorimotor domain) in a repertoire of behaviors consistently superior to the average of the other students, considering such factors as age, series or school production; and the frequency, intensity, and duration of these traits throughout their development. They are students with a talent for sports, capable of controlling and using the body in a productive and creative way, expressed in movements performed with great discernment. They are motivated and committed to physical activity, and demonstrate great fitness. The thesis defended is that the Brazilian legislation contemplates sport-gifted students as a target audience of Special Education, and these students need to be identified and attended by the school, in the regular class and in the specialized educational service. The problem is how that identification and follow-up can be accomplished. Was verified that in the schools studied there are no students identified and indicated for attendance. The objective is to understand the ideation of athletes, coaches and teachers of Physical Education at school, who contribute to the identification, referral and follow-up, in the school, of students with High Abilities/Gifted/Talent in Sports. The study was based on Gardner's Multiple Intelligences Theory (1994, 2000) and Renzulli's Three Ring Theory (2004). Concepts about Sport Talents in the Physical Education literature were also searched. This qualitative research, of applied nature, is located in the area of Special Education and covers Physical Education. The population and the research sample were composed of six athletes, six athletic trainers and six Physical Education teachers who work in two public schools of the city of Uberlândia (MG). In summary, the results revealed that it is necessary to seek interrelations between the knowledge of Special Education and Physical Education areas on the identification, referral and follow-up of people/students with high ability/gifted/sports talents; the terms high skills and/or gifted are not part of the daily life of the research participants, but the terminology of sports talent is familiar to them; it may be that the closest proximity to the term "talent" has to do with our history and the references made to talent, high ability and/or gifted in legislation documents that support Education, Physical Education and Sport in our parents; the ideation of the participants in the Special Education research are related to meeting the specificities of people with disabilities; the Physical Education teachers believe that it is not part of their job to identify, direct or accompany students with high ability. The teacher's commitment to attending to the specifics of the talented student is fundamental. We found teachers interested and dedicated to their work, however, it is understood, they need to know more about Special Education for students with sports talent.